Cardiovascular preventive activities and its associated factors among female nurses in Universiti Sains Malaysia Hospital - Mohamed, Nik Siti Fatimah (2017)
Introduction: It is well-accepted that nurses can be the community‟s role model in health education on cardiovascular disease risks reduction. Nevertheless, only nurses with good cardiovascular preventive activities practices may promote the benefits of healthy activities. Lack of study to our knowledge has addressed the important aspect of cardiovascular preventive activities among health care workers particularly nurses. Hence, this observational study was aimed to focus on prevalence of good cardiovascular preventive activities and its associated factors among female nurses in USM Hospital. Objective: To determine the prevalence of good cardiovascular preventive activities and its associated factors among female nurses in USM Hospital. Methodology: This is a cross-sectional study conducted from 1st June 2015 till 31st August 2015. Universal sampling was used among all registered nurses. Those who fulfilled the inclusion and exclusion criteria were included in the study. Only 215 of 1140 nurses fulfilled the criteria and were agreed for this study. However, 3 out of 215 were refused to answer the questionnaire, which makes the response rate of 98% (n=212). The nurses were requested to answer a set of self-guided questionnaire. Only those who practiced all 8 of the preventive activities were considered as having a good practice. Results: The overall good cardiovascular preventive activities among nurses were 14.2% (95% CI: 9.50, 18.90). The multivariate analysis revealed good cardiovascularpreventive activities was significantly associated with the department of working. Compared with nurses in surgical department, nurses from medical-based department had 0.2 odds of practicing good cardiovascular preventive activities (p-value = 0.015; 95% CI = 0.08, 0.76) and intradepartmental nurses had 0.3 odds of practicing good cardiovascular preventive activities (p-value = 0.010; 95% CI = 0.13, 0.76). There was no association between other sociodemographic factors (age, marital status, and education), work-related factors (shift work) and medical factors (family history of cardiovascular disease and perception of health status) with good cardiovascular preventive activities among female nurses both by simple and multiple logistic regressions. Conclusion: Prevalence of female nurses with good cardiovascular preventive activities was low in USM Hospital. Nurses from intradepartment and medical-based department had less likelihood to practice good cardiovascular preventive activities. This finding confirms the need for further research to determine the possible barriers for practicing these screening activities. Further effort to educate all the nurses on the importance of these screening activities and reduction of cardiovascular disease risk factors need to be developed and implemented.